2003
DOI: 10.1002/ss.75
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Multiple Needs Through Innovative Facility Design

Abstract: Designing buildings that incorporate and integrate a number of departments and functions is one way that colleges and universities are balancing financial challenges and facility needs. These buildings can transform the campus, but they require planning and coordination from a carefully assembled design team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Hence, on one hand we found that financial issues, sustainability, location regarding dinning and parking facilities, and proposal of common spaces are the most common factors used to make design decisions in residence halls design. Furthermore, the key finding from the design decision making point of view was that common spaces are usually proposed to enrich students' life by offering leisure, mentoring, and studying spaces (Balogh, Grimm and Hardy, 2005;Banning and Kuk, 2011;Deninger and Swift, 2009;Li, Sheely and Whalen 2005;Price 2003;Riker and Decoster 2008;Romano and Hanish 2003). On the other hand, the main issues that emerged regarding residence hall evaluations were administrative and technological issues, renovation and maintenance, special population needs, parent involvement, creation of learning communities, multicultural issues, staff issues, students' satisfaction and success, and sense of place of belonging (Amole 2009;Brandon, Hirt and Cameron, 2008;Carrol et all., 2003;Johnson and Cavins 2006;Najib, Yusof and Osman 2011;Thomsen and Eikemo 2011).…”
Section: Literature Review Of Housing Issuesmentioning
confidence: 99%
“…Hence, on one hand we found that financial issues, sustainability, location regarding dinning and parking facilities, and proposal of common spaces are the most common factors used to make design decisions in residence halls design. Furthermore, the key finding from the design decision making point of view was that common spaces are usually proposed to enrich students' life by offering leisure, mentoring, and studying spaces (Balogh, Grimm and Hardy, 2005;Banning and Kuk, 2011;Deninger and Swift, 2009;Li, Sheely and Whalen 2005;Price 2003;Riker and Decoster 2008;Romano and Hanish 2003). On the other hand, the main issues that emerged regarding residence hall evaluations were administrative and technological issues, renovation and maintenance, special population needs, parent involvement, creation of learning communities, multicultural issues, staff issues, students' satisfaction and success, and sense of place of belonging (Amole 2009;Brandon, Hirt and Cameron, 2008;Carrol et all., 2003;Johnson and Cavins 2006;Najib, Yusof and Osman 2011;Thomsen and Eikemo 2011).…”
Section: Literature Review Of Housing Issuesmentioning
confidence: 99%
“…First impressions of the campus matter; quality facilities influence enrollment decisions, while missing, inadequate or poorly maintained facilities lead students to reject potential colleges (Reynolds & Cain, 2006). In particular, research consistently establishes the importance of student unions / student centers in attracting student enrollments and keeping students on campus (Henry, 2004;Reynolds & Cain, 2006;Romano & Hanish, 2003). The student union holds a deep value for students, symbolizing a student-centered institution (Reynolds & Cain, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Research consistently establishes the importance of student unions / student centers in attracting student enrollments and keeping students on campus (Henry, 2004;Reynolds & Cain, 2006;Romano & Hanish, 2003). Given that one-fifth to one-third of students will reject a prospective college based on absent, inadequate or poorly maintained facilities (June, 2006), it is important that the student union not only provide the services that students need and want, but the environment (physical, human aggregate, organizational and created) should be consciously designed to help attract and retain students as well.…”
Section: The Importance Of Student Unionsmentioning
confidence: 99%
See 2 more Smart Citations